2013
DOI: 10.3233/ch-131690
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related increase in whole blood viscosity includes different profiles according to fat localization

Abstract: In a precedent study we observed that overall adiposity evaluated with the body mass index (BMI) was correlated with plasma viscosity and red blood cells (RBC) aggregation while abdominal obesity as assessed with the waist to hip ratio (WHR) was correlated with hematocrit. We investigated this issue in 129 women (age 15-65 years, BMI: 15 to 44 kg/m 2 , WHR: 0.65 to 1.13, fatness: 12-58%) who were divided into fatness groups: 17 underweight women (BMI <18.5), 75 normal weigh (BMI 18.5-24.9), 11 overweight (BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 40 publications
3
35
0
2
Order By: Relevance
“…This difference in RBC aggregation according to sex was already reported using ex vivo laser backscatter measurements [34]. On the other hand, a relation between obesity and erythrocyte aggregation has also been described [35][36][37]. The current cohort was composed of healthy participants having a BMI around 25 and did not include obese individuals.…”
Section: Limitationssupporting
confidence: 60%
See 1 more Smart Citation
“…This difference in RBC aggregation according to sex was already reported using ex vivo laser backscatter measurements [34]. On the other hand, a relation between obesity and erythrocyte aggregation has also been described [35][36][37]. The current cohort was composed of healthy participants having a BMI around 25 and did not include obese individuals.…”
Section: Limitationssupporting
confidence: 60%
“…Participants were lying down on an exam bed and ultrasound data were acquired on the palmer side of the forearm on the antebrachial vein, and on the tibial vein on the front of the leg. Ultrasound acquisitions were performed with a high-frequency scanner (Vevo770, 35 MHz central frequency probe #RMV-703, Visualsonics, Toronto, Canada). For each measurement site, veins with a diameter larger than 1 mm were quested to facilitate ultrasound post-processing.…”
Section: Subject Recruitment and Protocolmentioning
confidence: 99%
“…The reason for using BF% instead of BMI to represent the body fat content was that BF% is a better predictor for body fat mass based on age and gender [19,31]. Studies have shown that some erythroid-related hematologic parameters, such as RBC count, Hb, and HCT, were significantly positively correlated with waist to hip ratio and waist circumference [32,33]. In the present study, we also observed that BF%, TC, and TG are significantly positively associated with erythroid-related hematologic parameters in linear or r-shaped dose-response patterns, and workers with fatty liver disease had higher RBC count, Hg concentration, and HCT% than their non-diseased counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of the effects of fat content on erythroid-related hematologic parameters may hinge upon membranes of erythrocytes, which are rich in polyunsaturated fatty acids, being very sensitive to changes in fat content in vivo [34]. Excessive fat content may cause abnormal counts and function of RBCs by affecting their membrane composition, fluidity, and rheology [32].…”
Section: Discussionmentioning
confidence: 99%
“…hematocrit and hemoglobin, were significantly higher in DD pigs over almost the whole time-course, making the finding more robust. High levels of hematocrit and hemoglobin are associated with obesity and metabolic syndrome 36,37 , respectively, and both metrics are related to insulin resistance, NAFLD and NASH in humans [38][39][40] . Mean corpuscular volume was also higher in DD pigs; however, even though this parameter is increased in some liver pathologies, it does not seem to be linked to NAFLD 41 .…”
Section: Discussionmentioning
confidence: 99%